Biopetrol synthesized from oleic acid heterogenous Catalytic cracking by using granular metal as catalyst - Omar Syah Jehan, Elham (2010)
a Current petrol disaster and valuable oleic acid loss by disposal to environment are the reason why that biopetrol should be synthesized from oleic acid. Biopetrol is defined as liquid or gas that can be produced from natural vegetable oil or fat which has the same characteristic with commercial petrol in terms of its molecular structure. Oil palm is widely grown in Malaysia, palm oil has attracted the attention of researcher to develop an environmental friendly and high quality fuel, free from nitrogen and sulfur. The objective of this study is to determine concentration of synthesized biopetrol (dominated by isooctane) obtained. Catalytic cracking process is used to synthesize isooctane, using cooper as catalyst. Oleic acid is naturally in liquid form, so oleic acid is directly heated in the range of temperature 90O C-100O C for 2 hours in order to obtain isooctane, with catalyst is in moving form. Various rotation speeds are used in this study which is 600 rpm, 700 rpm, 850 rpm and 1000 rpm. The sample will be analyzing with Gas Chromatography (GC) with the Fire Ionization Detector method (FID). The sample will be compare with the retention time of standard calibration of pure isooctane in order to determine the actual concentration of isooctane in sample. The desired isooctane obtain is around 0.04201% - 0.16302% in the distilled oleic acid, with the presence of hexane as dilution solvent. After applying back calculation to obtain actual concentration the highest concentration of desired isooctane in oleic acid distillate is 44.94% at 700 rpm.